Sosialisasi Pencegahan Penyalahgunaan Narkotika Universitas Puangrimaggalatung - Burhanuddin Burhanuddin; Syupriadi Mujibu; Iwan Mamminanga; Erna Erna; Ekayani Burhanuddin Maspawati; Sitti Hartini Syupriadi (Institut Nalanda, 2025)
Laws are created to minimize crimes or violations and to uphold justice, in order to create a harmonious, peaceful, prosperous life, and provide a sense of security in social life. This service aims to provide insight and knowledge to students about the dangers of drug abuse and the adverse effects it causes. The socialization activity was attended by 30 students and students and 1 accompanying teacher located at Universitas Puangrimaggalatung . For this reason, through this Socialization of Prevention of Juvenile Delinquency (Narcotics Abuse) activity, it is able to increase students' understanding of the types of drugs, the impact of drug abuse from the physical, psychological, educational, social and economic aspects as well as how to prevent and overcome drug abuse among adolescents, especially students of Universitas Puangrimaggalatung . Community service to students of the school shows the level of understanding and awareness of the students on the importance of awareness to avoid drugs. With the growing awareness of Universitas Puangrimaggalatung students not to consume drugs, it is hoped that more or less it can reduce the number of drug use among students in Indonesia.